Cultural Heritage Preservation and Manuscript Conservation: Safeguarding the Laklak Batak Manuscript of Batak Culture in Indonesia - Sihotang, Marsono Marsel; Sitanggang, Tuntun (Insan Akademika Publications, 2022)
The Laklak Batak Manuscript, an invaluable repository of Batak culture and history, stands as a testament to the enduring significance of cultural heritage preservation. This research endeavors to safeguard the manuscript from the environmental, physical, and neglectful threats it faces, while also celebrating its profound cultural and historical significance. The research methodology encompasses a multidisciplinary approach, combining skilled conservation, climate-controlled storage, digitization, and active community engagement. Collaborations with experts, institutions, and local communities play an essential role in these preservation efforts, transforming the manuscript's condition from vulnerability to resilience. The current condition of the manuscript reflects meticulous restoration and an optimal storage environment, ensuring its structural integrity and visual quality. Ongoing preservation initiatives continue to enhance access, awareness, and appreciation of this living cultural treasure. In conclusion, the Laklak Batak Manuscript is not just a relic; it is a bridge connecting the past to the future, facilitating an enriched understanding of Batak culture and history. This research serves as a model for the preservation of cultural heritage, underscoring the importance of safeguarding linguistic, artistic, and historical legacies that enrich our collective human experience.